A Theory of Popular Power. Issue 2 (August 2022) - Field, Sandra Leonie
Abstract : I propose a theory of popular power, according to which a political order manifests popular power to the extent it robustly maintains an egalitarian basic structure. There are two parts to the theory. First, the power of a political order lies in the basic structure's robust self-maintenance. Second, the popularity of the political order's power lies in the equality of relations between the society's members. I will argue that this theory avoids the perverse consequences of some existing radical democratic theories of popular power which focus on mass expression, either in plebiscites or in social movements, as popular power's canonical instances. In particular, my theory does not valourise momentary expression over durable effect, and it offers a ready framework for conceptualising the sometimes-oligarchic substructure of the supposedly canonical instances of popular power. I will show that this theory has strong precedents within a certain republican tradition of political philosophy. 1